FINANCIAL PERFORMANCE ANALYSIS OF COOPERATIVE CREDIT ANNA POGUNG IN YOGYAKARTA - Rahayu, Suti; Lastari SE.,MM, Siwi (Management, 2010)
Suti Rahayu (2008). Analysis on Financial Performance of Anna Credit Union in Pogung Dalangan Yogyakarta, Year 2003-2006. Graduate Thesis, Management Study Program, STIE Nusa Megarkencana Yogyakarta. This research was aimed at knowing financial performance of Anna Credit Union in terms of the assessment of high-perform cooperative criterion of the year 2003 – 2006. The employed method of research was descriptive research; type of data required was secondary data. Data collecting techniques included interview and documentation, including organization aspect, business aspect and cooperative effect aspect. Result of the research concluded that organizational aspect of the year 2003-2006 was good but there was slight change in terms of member obligations. Business aspect of the year 2003-2006 was good but there was still scores 0 for asset turnover, business volume and liquidity factors. In the assessment of high-perform cooperative in 2003, Anna Credit Union got the score of 82.9, which was of good mark; in 2004 it got 78.9, decreasing 4 point but it was still of good mark; in 2005 it got score of 83.6, increasing 4.7 points with good mark and in 2006 it scored 82.3, which was good but it decreased 1.3 points compared to that of 2005 score. Keywords: financial performance, high-performance cooperative